Copper oxide stabilized oxy-functionalized boron nitride‑carbon nanotube nanohybrid: An ultra-stable electrode for flexible asymmetric supercapacitor device in ionic electrolyte. (1st December 2022) - Maity, Chandan Kumar; De, Shrabani; Acharya, Sourav; Siddiki, Salim Hassan; Sahoo, Sumanta; Verma, Kartikey; Thakur, Vijay Kumar; Nayak, Ganesh Chandra
Abstract: This work explores the smart combination of functionalized boron nitride (mK -BN) and carbon nanotube (CNT), stabilized with copper oxide (CuO), as a highly stable, flexible supercapacitor electrode in low-cost viable ionic electrolyte. Oxy-surface modified boron nitride (BN) was introduced to induce supplementary acceptor and donor energy levels for charge transport. Incorporation of CNT facilitated the charge storage through EDLC mechanism and also reduced internal resistance. In three-electrode analysis, CuO/mK -BN/CNT nanohybrid exhibited specific capacitance (Csp ) of 425 F/g in aqueous KCl. An asymmetric supercapacitor (ASC) device using CuO/mK -BN/CNT as cathode achieved a Csp of 80 F/g and 36 Wh/kg energy density with ⁓88 % stability after 25, 000 charging-discharging cycles in organic electrolyte. To further boost the capacitive performance, energy density, and rate capability of the ASC device, a low-cost, solvent free, and viable ionic electrolyte [(NEt3 H) + (HSO4 ) − ] was introduced. In ionic electrolyte, device showed a maximum Csp of 132 F/g with an enhanced energy density of 59.4 W h/kg. ASC devices in ionic electrolyte also exhibited superior volumetric energy density of 1.410 mW h/cm 3 and excellent electrochemical performances after connecting two cells in parallel or in series combination implying the capability of the device to produce different required capacitance and potential for practical application. Finally, a flexible ASC device with the ionic electrolyte was also tested. This work established that with the smart combination of additional energy level induced functionalized BN, conducting nanotubes, and pseudocapacitive CuO, a highly stable, flexible asymmetric supercapacitor device can be fabricated with high energy density. Graphical abstract: Unlabelled Image Highlights: Oxy-functionalization on boron nitride nanosheets to incorporate the additional acceptor and donor levels of charge carrier for supercapacitor electrode. CuO stabilized oxy-functionalized Boron Nitride-CNT nanohybrid (CuO/mK -BN/CNT), as positive electrode for asymmetric supercapacitor (ASC), achieved an energy density of 59.4 W h/kg in ionic electrolyte. ASC device exhibited good volumetric energy density of 1.410 mW h/cm 3 in ionic electrolyte. ASC devices revealed excellent electrochemical performances after connecting two cells in parallel or in series connections. Flexibility of ASC device studied in ionic electrolyte.